Measurements of radiocesium in animals, plants and fungi in Svalbard after the Fukushima Daiichi nuclear power plant disaster. Issue 12 (December 2019) - Mezaki, Yoshihiro; Kato, Shigeaki; Nishikawa, Osamu; Takashima, Isao; Tsubokura, Masaharu; Minowa, Haruka; Asakura, Tadashi; Matsuura, Tomokazu; Senoo, Haruki
Abstract: An earthquake struck the eastern part of Japan on March 11, 2011. The Fukushima Daiichi nuclear power plant was severely damaged by the earthquake and subsequent tsunami, leading to the emission of large amounts of radioactive pollutants, including 134 Cs and 137 Cs, into the environment. From August 23 to September 1 in 2011, and from August 27 to September 4 in 2013, we collected samples of animals, plants, fungi and lichens from Svalbard, Norway and measured the radioactivity of 134 Cs and 137 Cs contained in the samples. Though no radioactivity of 134 Cs, which has a half-life of approximately 2 years, was observed, radioactivity of 137 Cs, which has a half-life of approximately 30 years, was observed in some samples of lichens and fungi. We failed to detect the radioactivity of 134 Cs in any of the samples we collected, therefore, it was impossible to say clearly that the radioactivity is derived from Fukushima or not. Nevertheless, the radioactivity data documented in this report are a useful reference for the future surveys of radioactivity within the Arctic. Abstract : Environmental science; Environmental radioactivity; Water pollution; Bioaccumulation; Aquatic biology; Quality of life; Svalbard; Arctic; Cesium; Radioactivity; Fukushima Daiichi nuclear power plant.